Trends in retail centres recycling initiatives - Baharum, M.R.; Pitt, M.R.; Riley, M.L. (2010)
The paper intended to examine recycling initiatives of a group of UK retail centre in regards to the waste production and recycling initiatives over periods of two years. Method adopted in the study is the collection of primary data obtained from individual shopping centres throughout UK. Review of nine shopping centres merely represents the recycling trends of UK shopping centres, as few shopping centers have only just started their recycling programs. Findings of the study revealed that the sector did show an overall decreasing level of waste production, and waste minimisations were achieved through a variety of recycling initiatives. As a result, the more proficient approach to recycling, the better was the results. The paper also shows that shopping centre recycling does produce positive results. Although the effect of the landfill tax is uncertain but additional incentives and facilities management discipline to shopping centre recycling may be essential to drive the sector wide improvement.